PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEMEN PADANG PADA PT. SUMBER NIAGA INTERINDO (DISTRIBUTOR) - Doni Marlius; Muhammad Rayfael Shah Putra (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This research aims to analyze the influence of quality product, price, and promotion towards purchasing decisions of Padang cement products at PT. Sumber Niaga Interindo (Distributor). Data that used in this research is collect from consumers who used Padang cement products at PT. Sumber Niaga Interindo by total sampling method in selecting the sample. There are 32 sample of consumers who used cement products at PT. Sumber Niaga Interindo. Data processing use multiple linear regression method. The results of this research shows that quality of product has no positive and significant influence to purchasing decisions with a t-count value smaller than t-table -0.649 <2.048, price has no positive and significant influence on purchasing decisions with a t-count value smaller than t-table 1.403< 2.048. Meanwhile, promotion has a positive and significant influence on purchasing decisions of Padang cement products at PT. Sumber Niaga Interindo (Distributor) with a t-count value bigger than t-table 3,387>2,048